Comparison of decline in different cognitive domain in patients with normal pressure hydrocephalus - Rýdlo, Ondřej; Bubeníková, Adéla; Häcklová, Klára; Skalický, Petr; Leško, Róbert; Ebelová, Adéla; Netuka, David; IIIrd, Vladimír Beneš; Beneš, Vladimír; Bradáč, Ondřej (Neurosurgical review, 2024)
We sought to describe the cognitive profile of patients with Idiopathic Normal Pressure Hydrocephalus (iNPH) using a comprehensive neuropsychological battery. Based on age and education correlated norms, we aimed to compare performance in each measured cognitive domain: executive functions (EFs), verbal memory (VM), non-verbal memory (nVM), visuoconstructional abilities (VA) and attention/psychomotor speed (A/PS). Patients diagnosed with iNPH underwent comprehensive neuropsychological evaluation before shunting. Their performance was compared to the age and education correlated norms. Correlation of different cognitive domains in iNPH profile was performed. A total of 53 iNPH patients (73.21 ± 5.48 years) were included in the study. All of the measured cognitive domains were significantly damaged. The most affected domains were EFs and VM (p<0.001 and p<0.001, respectively). A/PS domain was affected milder than EFs and VM (p<0.001). The least affected domains were nVM (p<0.001) and VA (p<0.001). Patients with iNPH are affected in all cognitive domains and the cognitive decline is uneven across these domains. The impairment of memory was shown to depend on the presented material. VM was shown to be much more severely affected than nVM and along with VM, EFs were shown to be the most affected. A/PS speed was shown to be less affected than VM and EFs and the least affected domains were nVM and VA.
Keywords: normotenzní hydrocefalus; exekutivní funkce; Humans; neuropsychologické testy; Executive Function; Neuropsychological Tests; lidé; Hydrocephalus, Normal Pressure; Cognition; kognitivní dysfunkce; kognice; Cognitive Dysfunction